(untitled) (The International Journal for Scientific Research, 2024)
The world today is witnessing a tremendous technological development that greatly affects various aspects of practical life, including project management. In light of this development, modern technologies have become an essential tool for improving project management competencies and enhancing the overall performance of companies. This study aimed to explore the impact of modern technologies on project management competencies in technology companies in the Kingdom of Saudi Arabia. This study seeks to achieve the following objectives: - Analyze the impact of modern technologies: such as artificial intelligence, cloud computing, and big data analytics on project management competencies. - Identify the key benefits that companies achieve by adopting these technologies in project management processes, such as improved planning, execution, and risk management. - Explore the challenges and obstacles that technology companies in the Kingdom face when adopting modern technologies in managing their projects, including costs and training needs. - Provide recommendations to technology companies to improve the use of modern technologies in enhancing project management competencies.